Navigating Challenges in Sarawak’s Quail Farming Industry - Riesshen, Singh; Amir Haikal, Mohd Muzni; Claudina Rinya, Abu; Husna, Fathi; Ashby Sunang, Maseri; Hung Hui, Chung (UNIMAS Publisher, 2025)
Biotechnology becomes an important force in poultry husbandry, greatly improving quail populations’ production, health, and breeding. By investigating biotechnology insights in quail husbandry, the distance between theory and actual practice in poultry farm operations is reduced. Scientifically known as Coturnix coturnix, quails are becoming increasingly valuable for their nutritional and economic benefits, which has led to an increase in quail farming.